ORIENTASI TAFSIR RAMAH GENDER DI MAJLIS TA’LIM MASJID AN-NUR, BABELAN BEKASI - Aldomi Putra; Salman Faris; Muslimah Paxia Ilyas; Muhammad Hariyadi; Ahmad Zulki; Panggih Widodo (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
Sharia law found in the Qur'an still requires interpretation and has the potential to evolve. Abdullahi Ahmed An-Na'im answers the gap between sharia and issues of modernity. The deconstruction of sharia is used in the problem of Islamic law with current issues using an analytical knife in the form of Mahmud Thaha's theory of legal evolution, the theory of nasikh mansukh, Makiyyah and Madaniyyah, the meaning of gender texts and the concept of sharia on human rights. All Muslims in the world have the right to apply Islamic law as long as it does not violate the rights of other people, other groups or other religions